Five-year Reoperation Rates and Causes for Reoperations Following Lumbar Microendoscopic Discectomy and Decompression. Issue 1 (1st January 2020) - Aihara, Takato; Endo, Kenji; Sawaji, Yasunobu; Suzuki, Hidekazu; Urushibara, Makoto; Kojima, Atsushi; Matsuoka, Yuji; Takamatsu, Taichiro; Murata, Kazuma; Kusakabe, Takuya; Maekawa, Asato; Yamamoto, Kengo
Abstract : Study Design: Retrospective study of prospectively collected outcome data. Objective: The aim of this study was to investigate reoperation cases and determine whether or not the experience period of a single surgeon was associated with the causes of reoperations following lumbar microendoscopic discectomy for disc herniation (MEDH) and microendoscopic decompression for spinal stenosis (MEDS). Summary of Background Data: There have been few studies that investigated reoperation cases following MEDH and MEDS. Methods: Between June 2005 (first experience of MEDH) and September 2013, the same surgeon had been using MEDH and/or MEDS on 441 consecutive patients. The follow-up rate was 89.3%. The causes and rates of reoperations (RORs) were determined at 5 years after the initial operations. We also investigated the experience period of a single surgeon (EPS, interval between June 2005 and initial operation: median, 37 months). Results: The 5-year reoperation rate for all patients combined was 12.4% (49/394). The main causes for reoperations were recurrence of disc herniation (ROR, 7.01%) and increase of postoperative spondylolisthesis and/or instability (ROR, 9/394 = 2.28%); two of the nine cases were caused by excessive decompression, and the EPSs were 11 and 16 months. The other causes for reoperations were postoperative epidural hematoma (ROR, 0.76%; median EPS, 20 months), insufficient decompression (ROR, 0.25%; EPS, 17 months), and residual segmental scoliosis (ROR, 7.69%); two segmental scoliosis cases did not provide relief from sciatica, and therefore L4/5 transforaminal interbody fusions were performed. Conclusion: Postoperative epidural hematoma and excessive or insufficient decompression were often observed in the initial series of patients as the causes for reoperations. We think that it is important to be aware of and prevent such potential problems in any initial series of patients, as there are limitations to any surgical indications for the use of microendoscopic decompression for degenerative segmental scoliosis because of original traction and/or kinking of nerve roots. Level of Evidence: 4 Abstract : The 5-year reoperation rate following lumbar microendoscopic discectomy and decompression was 12.4%. Postoperative epidural hematoma and excessive or insufficient decompression were often observed as the causes of reoperations in the initial series of patients. There is surgical indication limitation to the use of microendoscopic decompression for degenerative segmental scoliosis.